DOES HEALTHCARE FACILITY DISTANCE HAVE INFLUENCE ON HUMAN CAPITAL DEVELOPMENT? EVIDENCE FROM NORTHWEST NIGERIA - ZAINAB, ABUBAKAR; OMOTAYO, LAWAL WASIU (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
Over the years, the issue of healthcare facility distance has been hampering the growth of Nigeria’s human capital, particularly in the country’s north. This study looked at how human capital development in North West Nigeria was affected by maternal mortality as measured by the distance to healthcare facilities. Using cross-sectional data from a field survey that involved distributing a questionnaire to a sample of 1383 respondents in three states in North West Nigeria, the study used the binary logistic model with a focus on women of reproductive age. The logistic model’s findings showed that while transportation has a positive and considerable impact on human capital development, healthcare facilities that are far from homes and the distance that prevents access to them have a positive but negligible impact. The study recommended the need for provision of feeder roads and means of transport to healthcare facilities in order to enable health seekers get to the healthcare centres promptly. Also, there is need to educate and financially empower women so that they can go to the healthcare center when the need arises